2014
DOI: 10.1186/1471-2393-14-90
|View full text |Cite
|
Sign up to set email alerts
|

Adverse birth outcomes among deliveries at Gondar University Hospital, Northwest Ethiopia

Abstract: BackgroundAdverse birth outcomes are major public health problems in developing countries. Data, though scarce in developing countries including Ethiopia, on adverse birth outcomes and the risk factors are important for planning maternal and child health care services. Hence, this study aimed to determine the prevalence and associated factors of adverse birth outcomes among deliveries at Gondar University Hospital, Northwest Ethiopia.MethodsInstitution based cross-sectional study was conducted in February 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
165
10
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(236 citation statements)
references
References 17 publications
58
165
10
3
Order By: Relevance
“…This is similar with study done in Tanzania which indicates that low hemoglobin level is associated with the occurrence of low birth weight [8]. This might be low Hb levels during pregnancy leads to intra-uterine oxygen inadequacy and reduced iron stores, causing infantile anemia before the age of six months.…”
Section: Controls N=258(%)supporting
confidence: 78%
“…This is similar with study done in Tanzania which indicates that low hemoglobin level is associated with the occurrence of low birth weight [8]. This might be low Hb levels during pregnancy leads to intra-uterine oxygen inadequacy and reduced iron stores, causing infantile anemia before the age of six months.…”
Section: Controls N=258(%)supporting
confidence: 78%
“…The overall prevalence of LBW in this study was 10 %. This is slightly lower than LBW estimates from Ethiopia (11.2 %) [47]. Similarly, this finding is far lower than reports from other Ethiopian studies [53, 54].…”
Section: Discussioncontrasting
confidence: 68%
“…Other studies have also observed a decrease and even absence of adequate prenatal care as it adds laboratory and clinical tests (2,(19)(20)(21) , indicating that the recent public programs, national or state, Stork Network (22) and Paranaense Mother (23) , advocating increased vigilance during pregnancy, have not yet reached their goals, drawing attention to the need for implementation of the preestablished protocols and strict observation of needs and characteristics specific of the assisted population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies highlight proper prenatal care as a determining factor in preventing maternal and child morbimortality (1)(2)(3) , as it contributes to more favorable outcomes from the accomplishment of the basic procedures such as conducting clinical and laboratory tests and monitoring the pregnancy through regular visits that enable detection and timely treatment of risk factors that bring complications for the mother and child health.…”
Section: Introductionmentioning
confidence: 99%